Scientific capacity building across borders in Latin America: A case study on inclusion - Romero, L. (2017)
The UNESCO World Conference on Higher Education 2009 will focus on how new dynamics of higher education can impact societal change in terms of inclusion . In this sense, the main problem Latin-American universities have to face in the sub-continent is scientific capacity building, the main obstacles to which are related to the brain drain and the way Ph.D. programs across borders are being run between developed and developing countries. This chapter presents a case study of scientific capacity building based on collaborative Ph.D. programs across borders and research incubator development, whose patterns and backgrounds could be very effective in avoiding brain drain and playing a key role in socio-economic growth. An exponential effect can be obtained via university networks in the continent and the development of the Latin American Space of Higher Education. The chapter discusses how a paradigm shift in Ph.D. studies across borders and a wide-scale application of real scientific development in the Third World can lead to reduction of many socio-economic gaps.